2011
DOI: 10.1111/j.1528-1167.2011.03200.x
|View full text |Cite
|
Sign up to set email alerts
|

Seizure frequency in pilocarpine-treated rats is independent of circadian rhythm

Abstract: SUMMARYPilocarpine-induced status epilepticus (SE) results in chronic spontaneous recurrent seizures resembling human temporal lobe epilepsy. In this and other experimental models, behaviorally monitored seizure frequency was suggested to vary in a circadian fashion, and to increase with time. We re-addressed those hypotheses using continuous video-electroencephalography (EEG) telemetry in rats with SE at 30 days of age. In 11 chronically epileptic animals monitored up to 300 days after SE in a fixed 12 h ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 13 publications
8
37
0
Order By: Relevance
“…As seen in human condition, seizure activity is highly variable among animals and occurs in clusters with seizures free-intervals 20,21 . Bajorat et al 21 using video-EEG in pilocarpine model identified three patterns of seizure distribution during the course of recording: a) > 3/day and evenly distributed seizures, b) > 2/day and again evenly distributed seizures and c) > 3/day and seizures clustered with seizure-free intervals. in our study, the average of seizures was 1.34 per week, being lower than observed by Bajorat et al 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As seen in human condition, seizure activity is highly variable among animals and occurs in clusters with seizures free-intervals 20,21 . Bajorat et al 21 using video-EEG in pilocarpine model identified three patterns of seizure distribution during the course of recording: a) > 3/day and evenly distributed seizures, b) > 2/day and again evenly distributed seizures and c) > 3/day and seizures clustered with seizure-free intervals. in our study, the average of seizures was 1.34 per week, being lower than observed by Bajorat et al 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Bajorat et al 21 using video-EEG in pilocarpine model identified three patterns of seizure distribution during the course of recording: a) > 3/day and evenly distributed seizures, b) > 2/day and again evenly distributed seizures and c) > 3/day and seizures clustered with seizure-free intervals. in our study, the average of seizures was 1.34 per week, being lower than observed by Bajorat et al 21 . we do not rule that the low accuracy of the video monitoring may have contributed to underestimate the seizure activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pilocarpine-treated rats exhibited twice as many spontaneous seizures during the light phase as compared to the dark phase, a rhythm that remained intact and governed by the clock even when animals were maintained in constant darkness (Quigg, 2000). However, a more recent study reported spontaneous seizures elicited by pilocarpine treatment in rats was independent of the circadian cycle (Bajorat et al, 2011), an effect likely due to dependence on underlying sleep architecture (Matos et al, 2010b). In a model of electrically-induced status epilepticus, dentate gyrus neurons exhibited enhanced electrical excitability that corresponded with the time of day of enhanced seizure susceptibility (Matzen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have video monitored all animals 12 h a day, 5 days a week, along the 9 months after status. These hours were preferentially at light time (7 am–7 pm) based on that no differences were reported in terms of clustered seizures or circadian rhythm for both KA and PILO models (51, 52). However, despite that, it is still possible that some spontaneous seizures were missed along the study, so future studies with more extensive monitoring could produce different results.…”
Section: Discussionmentioning
confidence: 99%